2011
DOI: 10.1016/j.jhealeco.2011.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Changing mix of medical care services: Stylized facts and implications for price indexes

Abstract: The utilization of health care services has undergone several important shifts in recent years that have implications for the cost of medical care. We empirically document the presence of these shifts for a broad list of medical conditions and assess the implications for price indexes. Following the earlier literature, we compare the growth of two price measures: one that tracks expenditures for the services actually provided to treat conditions and another that holds the mix of those services fixed over time.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
30
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 10 publications
3
30
0
1
Order By: Relevance
“…Overall, our findings are similar to those (Aizcorbe and Nestoriak ; Aizcorbe et al. ) who also found that the MCE grows slower than the SPI.…”
Section: Study Findingssupporting
confidence: 93%
See 2 more Smart Citations
“…Overall, our findings are similar to those (Aizcorbe and Nestoriak ; Aizcorbe et al. ) who also found that the MCE grows slower than the SPI.…”
Section: Study Findingssupporting
confidence: 93%
“…Expenditure shifts have been documented and quantified for specific diseases, such as cataracts, heart attacks, and depression . These shifts have also been shown when looking across a broad set of diseases as in the work by Aizcorbe and Nestoriak (), henceforth AN, and Aizcorbe et al. ().…”
Section: Introductionmentioning
confidence: 58%
See 1 more Smart Citation
“… 1 See, e.g., Bundorf, Royalty, and Baker (2009); Aizcorbe and Nestoriak (2011); Herrera et al (2013); Dunn, Liebman, and Shapiro (2014). There is also significant attention in this literature to whether improvements in health care quality might bias measures of prices: see e.g., Cutler et al (1998, 2001).…”
mentioning
confidence: 99%
“…5 The U.S. Bureau of Economic Analyses also studied the implementation of specifi c activity indices for health care. 3 The use of performance indicators to assess Brazilian public health organizations is rare. There is a growing trend toward outsourcing clinical laboratory analysis in SUS unmatched by proposals for performance evaluation in both the public network and third-party laboratories.…”
mentioning
confidence: 99%